An Econometric Analysis of Beef Cattle Supply Trends in West Papua Province, Indonesia - Pakage, Stepanus; Aronggear, Elan L; Widayati, Trisiwi W; Supriyantono, Andoyo (Faculty of Animal Science, Universitas Brawijaya, 2025)
Beef cattle play a strategic role in supporting food security and the regional economy in West Papua Province. This study aims to analyze the trend of beef cattle population growth and identify the factors influencing beef cattle supply in West Papua Province. A descriptive research design was employed, utilizing secondary data obtained from official sources. Trend analysis was applied to assess cattle population growth, while multiple regression analysis was conducted to examine the factors affecting beef cattle supply in the province. The analysis predicts that the beef cattle population in West Papua will continue to increase over the next ten years. The supply of beef cattle in West Papua is significantly influenced by the previous year’s production, current cattle population, slaughter rate, beef prices, Gross Regional Domestic Product (GRDP), human population, and the populations of goats and pigs.